Quality of life in patients with comorbidity of chronic pancreatitis and chronic obstructive pulmonary disease in presence of smoking - L. S. Babinets; О. S. Kvasnitska (Civic Union "Communicable Diseases Intensive Care Association", 2019)
Background. A combination of chronic pancreatitis and chronic obstructive pulmonary disease is quite common in clinical practice. This has a negative effect on the clinical course of both diseases. Smoking increases risk of chronic pancreatitis development. Purpose of the study. The purpose of this investigation is to learn smoking influence on clinical course and life quality of patients with comorbidity of chronic pancreatitis and chronic obstructive pulmonary disease. Material and methods. 141 patients with chronic pancreatitis with chronic obstructive pulmonary disease and without it had been examinated. 98 patients with chronic pancreatitis with chronic obstructive pulmonary disease were included to the main group. Both diseases were at phase of remission. Results and discussion. 29 (20.6 %) active smokers were among them. All of them are men. The main syndromes in patients with chronic pancreatitis with chronic obstructive pulmonary disease are dyspeptic (85.7%) and astenic (94.9 %), pain syndrome was registered in 83.7 % patients, the equivalents of pain were observed in 16.3 % of patients. Conclusions. Significant decreasing of life quality in patients with comorbidity of chronic pancreatitis and chronic obstructive pulmonary disease was proved: scales of physical functioning, role physical functioning and general health status were significantly decreased in patients with concomitant COPD (р <0.05). Analysis of the GSRS questionnaire revealed a significant (p <0.05) increasing in three of the five scales presented in patients with chronic pancreatitis and COPD, indicating a deterioration of quality of life in case of comorbidity. There were revealed significant decreasing of physical functioning scale and general health status scale (questionnaire SF‑36) and increasing of all scales in GSRS scales (except for the diarrheal syndrome scale). Significant (p <0.05) moderate correlations were found between the scales of physical functioning and role physical functioning and smoking experience, and moderate correlations with the smoking experience of the dyspeptic syndrome score.